1986
DOI: 10.1172/jci112310
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cardiac myosin isozymes in human conduction system. Immunohistochemical study using monoclonal antibodies.

Abstract: To determine the presence and distribution of cardiac myosin isozymes in the human conduction system, we performed an immunohistochemical study using monoclonal antibodies CMA19 and HMC14, which are specific for myosin heavy chains of human atrial type (a-type) and ventricular type (f-type), respec-tively. Serial frozen sections of human hearts were obtained from autopsy samples and examined by indirect immunofluorescence. a-type was found in all myofibers of sinus node and atrio-ventricular node, and in 55.2±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…The heterogeneity of myosin in the human heart has already been evidenced either with mono-or polyclonal antibodies (11,16,19,32). Each isoform has been related to a and 13 isoforms according to Hoh (13).…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of myosin in the human heart has already been evidenced either with mono-or polyclonal antibodies (11,16,19,32). Each isoform has been related to a and 13 isoforms according to Hoh (13).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the atrioventricular nodal cells coexpress both myosin isoforms in chickens, 47,85 cows, 86 and humans. 84,87 In the developing AVN of rats 82 and mice (authors' unpublished data, 1997), however, no expression of ␤-MHC was found, which may be a characteristic of small animals or merely reflect phylogenetic interspecies variation.…”
Section: Contractile Proteinsmentioning
confidence: 99%
“…Subsequently, this was also noticed in mammalian species, including rats, 157 rabbits, 158 cows, 86,158 and humans. 87 Initially, both isoforms are expressed in opposite gradients and only gradually become confined to either the atrium or ventricle. 6,11,47,81,159 Coexpression persists a relatively long time in the slow-conducting flanking segments (IFT, AVC, and OFT) but also in the fast-conducting TVC.…”
Section: Contractile Proteinsmentioning
confidence: 99%
“…In conditions of heart failure, there is a significant upregulation of the slower ␤-MHC isoform and a downregulation of the faster ␣-MHC isoform in rodents (15,20,35), and in human chronic heart failure, the expression of ␣-MHC is virtually absent (37,38,40,42,49). Furthermore, since the expression of ␣-MHC in mammalian hearts is more abundant in the LV epicardium than in the endocardium (6,7,12,33,48,49,62), shifts in the expression of ␣-MHC can have significant effects on the regional timing and strength of contractile function in the heart. An indepth understanding of the effects of contractile protein composition on myocardial function requires the characterization of regional myocardial wall motion in vivo.…”
mentioning
confidence: 99%